IMPACT OF SPATIAL FACTORS ON REVENUE AND EXPENDITURE OF HOUSING MAINTENANCE FUND: A CASE STUDY IN BEIJING - Weizheng Zhao (PEOPLE: International Journal of Social Sciences, 2026)
Housing maintenance is an integral component of sustainable urban governance. However, the revenue and expenditure of housing maintenance fund often vary across regions due to socioeconomic, built-environment, and ecological settings. The study of its spatial heterogeneity can be critical for understanding regional disparities, optimizing resource allocation, and improving governance efficiency. This study proposes categorizing research samples based on functional zones, 275 subdistricts/townships within three functional zones of Beijing were examined to explore the influence mechanisms of spatial factors on maintenance fund revenue and expenditure, then compares ordinary least square (OLS), geographically weighted regression (GWR), and multiscale geographically weighted regression (MGWR) models in analyzing the impact mechanisms of spatial factors. The conclusions are as follows: (1) Functional zones coincide with sample categories, showing significant differentiation and spatial autocorrelation, which underscores the role of Beijing's master plan. (2) MGWR performs better than other models: influence factors exhibit spatial heterogeneity in maintenance fund, GDP exerts the most significant impact on fund revenue, while population density most strongly affects fund expenditure. (3) Policy formulation should draw on ecological and socioeconomic factors to mitigate fund revenue losses, and leverage built-environment factors to improve housing maintenance.